Prognostic Value of Right Ventricular Dysfunction in Heart Failure With Reduced Ejection Fraction: Superiority of Longitudinal Strain Over Tricuspid Annular Plane Systolic Excursion. (January 2018) - Carluccio, Erberto; Biagioli, Paolo; Alunni, Gianfranco; Murrone, Adriano; Zuchi, Cinzia; Coiro, Stefano; Riccini, Clara; Mengoni, Anna; D'Antonio, Antonella; Ambrosio, Giuseppe
Abstract : Background—: In heart failure (HF) with reduced ejection fraction, right ventricular (RV) impairment, as defined by reduced tricuspid annular plane systolic excursion, is a predictor of poor outcome. However, peak longitudinal strain of RV free wall (RVFWS) has been recently proposed as a more accurate and sensitive tool to evaluate RV function. Accordingly, we investigated whether RVFWS could help refine prognosis of patients with HF with reduced ejection fraction in whom tricuspid annular plane systolic excursion is still preserved. Methods and Results—: A total of 200 patients with HF with reduced ejection fraction (age, 66±11 years; ejection fraction, 30±7%) with preserved tricuspid annular plane systolic excursion (>16 mm) underwent RV function assessment using speckle-tracking echocardiography to measure peak RVFWS. After a median follow-up period of 28 months, 62 (31%) patients reached the primary composite end point of all-cause death/HF rehospitalization. Median RVFWS was −19.3% (interquartile range, −23.3% to −15.0%). By lasso-penalized Cox-hazard model, RVFWS was an independent predictor of outcome, along with Eplerenone in Mild Patients Hospitalization and Survival Study in Heart Failure-HF score, Echo-HF score, and severe mitral regurgitation. The best cutoff value of RVFWS for prediction of outcome was −15.3% (area under the curve, 0.68; P <0.001; sensitivity, 50%; specificity, 80%). In 50 patients (25%), RVFWS was impaired (ie, ≥−15.3%); event rate (per 100 patients per year) was greater in them than in patients with RVFWS <−15.3% (29.5% [95% confidence interval, 20.4–42.7] versus 9.4% [95% confidence interval, 6.7–13.1]; P <0.001). RVFWS yielded a significant net reclassification improvement (0.584 at 3 years; P <0.001), with 68% of nonevents correctly reclassified. Conclusions—: In patients with HF with reduced ejection fraction with preserved tricuspid annular plane systolic excursion, RV free-wall strain provides incremental prognostic information and improved risk stratification.